The Relationship Between Fulfillment of Sexual Needs With Sexual Behavior Deviation to Male Prisoners at Second Class Prison on Bondowoso - Dini Ratifa; Titik Suhartini; Bagus Supriyadi (KHD Production, 2023)
The fulfillment of sexual needs is one of the physiological needs, no exception for prisoners. Deprived of everyday sex life, prisoners will result in sexual behavior deviation, where the distribution of sexual desire is sublimated in various abnormal ways. It is necessary to consider the need for the implementation of mechanisms for providing access to sexual needs in prison to prevent the occurrence of sexual irregularities in male prisoners, which in this case, will also protect the reproductive health of the legal partner/wife of the prisoner. This study aims to know the relationship between the fulfillment of sexual needs and sexual behavior deviation in male prisoners at second-class prisons in Bondowoso. This research uses a correlational analytical research design. Seventy-three respondents following this study and collected by purposive sampling. Data was collected using a questionnaire and processed with the Spearman rank test. The results of the analysis of the fulfillment of sexual needs are mostly not good, which is 66 people (90,4%), and sexual behavior is deviant mainly, which is 54 people (74%). The correlation coefficient analysis shows the value of fulfillment of sexual needs is 1.000 and sexual behavior deviation is 0.549. A significant linear relationship exists between the sexual need fulfillment variable and the sexual behavior deviation variable (p=0.000). Midwives must care and be able to provide counseling and education about risky sexual behavior to vulnerable groups, including prisoners. This activity aims to break the chain of transmission of STIs and HIV/AIDS due to deviant sexual behavior.